The Potential Role of 6-gingerol and 6-shogaol as ACE Inhibitors in Silico Study - Yohanes Bare; Maria Helvina; Gabriella Chandrakirana Krisnamurti; Mansur S (Biogenesis: Jurnal Ilmiah Biologi, 2020)
Hypertension has become the third highest cause of death in Indonesia. The condition is correlated with angiotensin-converting enzyme (ACE), and possibly managed with the use of drugs. In addition, some natural compounds, including 6-shogaol and 6-gingerol from ginger, are used to decrease blood pressure. However, the mechanism and binding site of these compounds to ACE protein is currently unclear. This study, therefore, aims to investigate the potential role of these compounds as an angiotensin-converting enzyme inhibitor. The ACE protein was downloaded from Protein Data Bank (PDB) database with the ID: 3bkk, while the 6-shogaol (CID: 5281794) and 6-gingerol (CID: 44559528) ligands were obtained from the PubChem database. Meanwhile, molecular docking was established using HEX 8.0.0 software. The analysis examined the amino acid residues and the bonds formed from these interactions. According to the results, 14 amino acid residues were formed by the interaction between 6-shogaol and ACE, while the interaction between 6-gingerol and ACE formed eight amino acids. Also, 13 amino acid residues in the novelty binding site of ACE were discovered to be blocked by the ligands from ginger. Therefore, the compounds have potential roles as inhibitors, and this possibly helps to prevent regulation of the renin-angiotensin system. These interactions also formed hydrogen bonds, as well as electrostatic, unfavorable, and hydrophobic sites, making the binding stronger than others.